Bipyrazole bearing ten nitro groups – a novel highly dense oxidizer for forward-looking rocket propulsions. Issue 30 (16th July 2018) - Dalinger, Igor L.; Suponitsky, Kyrill Yu.; Shkineva, Tatyana K.; Lempert, David B.; Sheremetev, Aleksei B.
Abstract : Novel high-density oxidizer based on highly nitrated bipyrazole was developed. It is the champion among heteroaromatic CHNO compounds with a density equal to 2.021 g cm −3 at room temperature. Abstract : Taking into account the manifold requirements for future rocket industry breakthroughs, the scientific community is currently focusing on the design of novel higher performance, high-tech and environmentally more acceptable materials compared with conventional propellant ingredients for liquid, solid, gelled, and hybrid propellant systems. Earlier, considerable efforts were made to find environmentally friendly chlorine free alternatives to ammonium perchlorate (AP) which is still the main oxidizer for solid propellants; however, success in this way is extremely rare. In this work, a novel oxygen-rich energetic material, 4, 4′, 5, 5′-tetranitro-2, 2′-bis(trinitromethyl)-2 H, 2′ H -3, 3′-bipyrazole (11 ), was obtained by N -alkylation of 4, 4′, 5, 5′-tetranitro-2 H, 2′ H -3, 3′-bipyrazole (9 ) with bromoacetone and subsequent nitration. X-ray single-crystal diffraction confirmed its structure and revealed a unique high crystal density of 2.021 g cm −3 at room temperature, introducing it into the top three of the densest CHNO compounds known. This high density material has an attractive positive oxygen balance, acceptable sensitivity, and enthalpy of formation (on a unit of weight) similar to CL-20, with calculated specific and effective impulses exceeding those of AP and ADN, making it a competitive replacement for AP as a green energetic oxidizer for diverse propellants.